ADCY5-related movement disorders: Frequency, disease course and phenotypic variability in a cohort of paediatric patients. (August 2017) - Carecchio, Miryam; Mencacci, Niccolò E.; Iodice, Alessandro; Pons, Roser; Panteghini, Celeste; Zorzi, Giovanna; Zibordi, Federica; Bonakis, Anastasios; Dinopoulos, Argyris; Jankovic, Joseph; Stefanis, Leonidas; Bhatia, Kailash P.; et al.
Abstract: Introduction: ADCY5 mutations have been recently identified as an important cause of early-onset hyperkinetic movement disorders. The phenotypic spectrum associated with mutations in this gene is expanding. However, the ADCY5 mutational frequency in cohorts of paediatric patients with hyperkinetic movement disorders has not been evaluated. Methods: We performed a screening of the entire ADCY5 coding sequence in 44 unrelated subjects with genetically undiagnosed childhood-onset hyperkinetic movement disorders, featuring chorea alone or in combination with myoclonus and dystonia. All patients had normal CSF analysis and brain imaging and were regularly followed-up in tertiary centers for paediatric movement disorders. Results: We identified five unrelated subjects with ADCY5 mutations (11% of the cohort). Three carried the p. R418W mutation, one the p. R418Q and one the p. R418G mutation. Mutations arose de novo in four cases, while one patient inherited the mutation from his similarly affected father. All patients had delayed motor and/or language milestones with or without axial hypotonia and showed generalized chorea and dystonia, with prominent myoclonic jerks in one case. Episodic exacerbations of the baseline movement disorder were observed in most cases, being the first disease manifestation in two patients. The disease course was variable, from stability to spontaneous improvement during adolescence. Conclusion: Mutations in ADCY5 are responsible for a hyperkinetic movement disorder that can be preceded by episodic attacks before the movement disorder becomes persistent and is frequently misdiagnosed as dyskinetic cerebral palsy. A residual degree of neck hypotonia and a myopathy-like facial appearance are frequently observed in patients with ADCY5 mutations. Highlights: ADCY5 mutational frequency in paediatric patients is unknown. 5/44 (11%) subjects in our cohort carried pathogenic ADCY5 mutations. Chorea-dystonia, exacerbations and developmental delay are often observed together. Disease course and clinical features are variable among patients with ADCY5 mutations. Residual cervical hypotonia and a myopathy-like face are additional diagnostic clues.